A STUDY OF JUVENILE CRIMES IN BORSTAL JAIL, FAISALABAD, PAKISTAN - A. Shamim; Z. Batool; M. I. Zafar; N. Hashmi (Journal of Animal and Plant Sciences, 2009)
Juvenile crimes is a popular issue of social research. Juvenile crimes slow down the development of a society. The present research aimed at exploring the socio-economic factors of juvenile crime. A sample of 90 juveniles was selected in Borstal Jail Faisalabad through random sampling technique. Study found that majority of the respondents was illiterate and belonged to the age group 16-18 years. Most of them belonged to low income group. This study concluded that poverty and low economic status promotes the rate of juvenile crimes.
Keywords: Juvenile crimes; socio-economic factors; attitude towards crime.